KADAR KLOROFIL DAUN PAKCOY (BRASSICA CHINENSIS L.) SETELAH PERLAKUAN PUPUK KANDANG DAN AMPAS TAHU SEBAGAI BAHAN AJAR MATA KULIAH FISIOLOGI TUMBUHAN - Wenno, Stenly Jacob; Sinay, Hermalina (BIOPENDIX: Jurnal Biologi, Pendidikan dan Terapan, 2019)
Background: Pakcoy (Brassica chinensis L.) is a vegetable plant originating from China that has leaf stalks that are wider and larger than green mustard greens. Pakcoy has nutritional value such as vitamin C, vitamin A, carbohydrates, fiber, protein, calcium, magnesium. Chlorophyll is a green leaf substance found in green parts of plants, especially on leaves. One of the factors that influence the chlorophyll content in pakcoy mustard leaves is the soil condition in this case the nutrient content and nutrients in the soil. One way to meet nutrient and nutrient content in the soil is by using organic fertilizers such as manure and tofu. Method: This study aims to determine the chlorophyll content of pakcoy leaves (Brassica chinensis L.) after giving manure and tofu dregs. Based on the analysis of chlorophyll content using the UV-VIS spectrophotometer method at wavelengths of 644 nm and 663 nm. Results: The highest levels of chlorophyll A in pakcoy (Brassica chinensis L.) leaves with PK3AT1 treatment (7 kg manure and 7 kg tofu dregs) of 2.007 mg / L, highest chlorophyll B levels in pakcoy (Brassica chinensis L.) leaves with treatment PK3AT3 (7 kg manure and tofu dregs 3 kg) at 2.674 mg / L, and the highest total chlorophyll content in pakcoy (Brassica chinensis L.) leaves with PK3AT1 treatment (7 kg manure and 7 kg tofu dregs) at 4,558 mg / L. Conclusion: Chlorophyll A, B and total levels in pakchoy (Brassica chinensis L.) leaves after a combination of manure and tofu dregs have high levels of different corophils.